Dietary mulberry-leaf flavonoids improve the eggshell quality of aged breeder hens - Huang, Zhenwu; Dai, Hongjian; Jiang, Jingle; Ye, Nanwei; Zhu, Shanli; Wei, Quanwei; Lv, Zengpeng; Shi, Fangxiong (Theriogenology, 2022)
Eggshell quality is subject to a significant decline in the late laying period, which results in huge economic losses. The purpose of this study was to investigate the effects of dietary mulberry-leaf flavonoids (MF) on the eggshell quality of aged breeder hens. A total of 270 (60-week-old) Qiling breeder hens were randomly assigned to 3 treatments with supplemental dietary MF doses (0, 30, and 60 mg/kg). The results showed that dietary MF improved the eggshell thickness and strength, following the reduced broken egg ratio (P < 0.05). Histological analysis showed that dietary MF increased glandular density and luminal epithelium height in the shell gland (P < 0.05). MF treatment reduced the apoptotic index of the shell gland, following by improved antioxidant capacity (P < 0.05). The protein expression of Caspase 3 was down-regulated, and Nrf2 was up-regulated by dietary MF (P < 0.05). Furthermore, calcium (Ca) content in the serum and shell gland, as well as the activity of Ca2+-ATPase in the shell gland were increased by dietary MF (P < 0.05). Ca transport-related genes (ESRα, ESRβ, KCNA1, OPN, CABP-28K and CDH6) in the shell gland were upregulated by dietary MF treatment (P < 0.05). In conclusion, dietary MF could ameliorate the eggshell quality of aged hens by improving antioxidative capability and Ca deposition in the shell gland of uterus. •Dietary Mulberry-leaf flavonoids (MF) can enhance the antioxidant capacity by activating Nrf2.•Dietary MF can alleviate aging-induced injury in the shell gland.•Dietary MF can enhance Ca ion transport in the shell gland of aged breeder hens.•Dietary MF improve eggshell quality of aged breeder hens.